(untitled) (Academia Journal of Medicine, 2021)
Background: Diabetes mellitus is a metabolic syndrome which has reached epidemic levels in both developed and developing parts of the modern world. With rising prevalence of obesity, physical inactivity and other related metabolic syndromes, the incidence and prevalence of type II DM is sharply increasing along with the related complications. Type II diabetes mellitus is related with macrovascular and microvascular complications, latter being usually overt. In fact, in many cases the type II diabetes often reaches clinical attention due to the microvascular complications. The common microvascular complications including diabetic retinopathy, diabetic nephropathy and sensory neurological deficits are a common cause of morbidity associated with type II diabetes. Aim: The frequency of microvascular complications in newly diagnosed cases of Type II diabetes mellitus. Subjects and Methods: More than 200 patients newly diagnosed cases of type II DM were included in the study conducted in Medicine Department of our Institution following approval from IEC and after obtaining written & informed consent. The frequency of the microvascular complications including diabetic retinopathy, diabetic nephropathy and diabetic sensory neuropathy was calculated utilizing various tests and clinical examination along with presence of hypertension and smoking, latter are known factors in increasing the severity of the type II diabetes related morbidities. Appropriate statistical methods and tools were used to find out the statistical significance of various observations. Observations and Results: Significant number of patients in our study were in 41-60yrs age group with male predominance. Majority were obese and more than three-fourth had deranged HbA1c levels of >6.5. Significant number of patients had hypertension and were smokers that showed statistical correlation with increased incidence of microvascular complications in the corresponding subgroup. Significant proportion of patients in our study group were detected with microvascular complications in form of diabetic retinopathy, diabetic nephropathy and sensory neuropathy. Conclusion: Since the incidence of microvascular complications including retinopathy, nephropathy and sensory neuropathy is quite high in newly diagnosed patients of Type II diabetes mellitus, hence clinical & laboratory tests directed to their diagnosis should be included in the screening protocol of such patients. As these tests are inexpensive, hence their inclusion may go a long way in reducing the microvascular complication related morbidity in type II diabetes mellitus patients.